2006
DOI: 10.1080/13697130600871947
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbances, oxidative stress and cardiovascular risk parameters in postmenopausal women complaining of insomnia

Abstract: Although all women complained of insomnia, 50% of them demonstrated apnea during polysomnography recordings. Of the parameters measuring oxidative stress, only TBARS levels were increased in our sample. Some clinical data, such as time of onset of menopause, may be associated with the oxidative stress status of these women, probably due to the lack of estrogen and to sleep disturbances, such as apnea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
1
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(44 citation statements)
references
References 31 publications
1
38
1
4
Order By: Relevance
“…As also observed in a study by Vagiakis et al (31), REM sleep latency was also longer in women than in men. Taken altogether, differences between genders could be due to the effects of cyclic levels of female reproductive hormones on sleep (20,32). Conceivably, this suggests that women are either more susceptible to clinical symptoms deriving from inadequate sleep or are more likely to report symptoms in general (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As also observed in a study by Vagiakis et al (31), REM sleep latency was also longer in women than in men. Taken altogether, differences between genders could be due to the effects of cyclic levels of female reproductive hormones on sleep (20,32). Conceivably, this suggests that women are either more susceptible to clinical symptoms deriving from inadequate sleep or are more likely to report symptoms in general (33).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, nightmares were twice as prevalent in women as in men (19). The reasons for such discrepancies are attributed to hormonal fluctuations over the menstrual or estrous cycles, a factor that has been associated with sleep variations in both humans and rats (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies in rats found that males display significantly more paradoxical sleep during both the day and the night than females [29,30], whereas another study in Swiss-Webster mice reported a slight diurnal sex difference in the amount of paradoxical and nonparadoxical sleep [31]. Additionally, hormonal fluctuation is a factor that has been associated with sleep variations in both humans and rats [32,33], although little information is available about how it affects sleep [34]. From a clinical perspective, women and men sleep differently and recover differently from sleep deprivation [35].…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have also linked oxidative stress with insomnia. For example, levels of thiobarbituric acid reactive substances were elevated in postmenopausal women with insomnia, although blood concentrations of catalase, superoxide dismutase, and glutathione were found to be normal (Hachul de Campos et al, 2006). In an investigation on participants with primary insomnia, significantly lower GSH-Px (selenium-containing antioxidant enzyme) activity and higher MDA levels were found compared with controls (Gulec et al, 2012).…”
Section: Sleep and Its Effect On Oxidative Stressmentioning
confidence: 99%